Chemical Modification of Natural Jordanian Zeolitic Tuff using Acetamide and N,N-Dimethylformamide - M. MUSLEH, SALEM; AZIZ AMRO, ABDUL; I. YOUSEF, RUSHDI (Asian Journal of Chemistry, 2010)
A low priced locally natural occurring zeolitic tuff was chemically treated with acetamide and N,N¢-dimethyl formamide (DMF) compounds. The chemical and structural properties of the treated and untreated tuff were studied using scanning electron microscopy (SEM), powder X-ray diffraction (XRD), X-ray fluorescence (XRF) and infrared spectroscopy (FTIR) techniques. The XRD data revealed that chemical treatments do not affect the mineral content of the zeolitic tuff. The results of SEM, XRF and FTIR techniques indicated some changes in the zeolite surface. The results of the uptake of Pb(II), Cd(II), Ni(II) and Cu(II) from their aqueous solutions for the zeolitic tuff samples revealed that treatment with acetamide increases slightly the removal ability of zeolitic tuff, while treatment with DMF decreases the tuff removal ability.